The capacity of islamic school principals in implementing the merdeka belajar (freedom to learn) program - Risna; Hanafi Pelu (12 Waiheru, 2024)
This article examines the role of Islamic school principals in implementing the Merdeka Belajar (Freedom to Learn) program. Employing a qualitative research approach that focuses on words and sentences, the study utilizes descriptive research to offer insights into the social context or to explore and clarify specific phenomena. The findings show that: 1) The Islamic school principals have a high level of enthusiasm for implementing Merdeka Belajar in Islamic Schools; 2) Islamic School principals play a critical role in delivering the Merdeka Belajar program within Islamic Schools, and the successful dissemination of this educational program largely depends on how intensively the principal communicates Merdeka Belajar within their Islamic Schools, 3) Islamic Schools principals believe that the socialization process, training, and technical guidance for the Merdeka Belajar (Freedom to Learn) program need to adhere to guidelines set by the Ministry of Education and Culture and the Ministry of Religious Affairs; 4) Only a limited number of Islamic Schools have implemented Merdeka Belajar; 5) IT resources and teachers' proficiency in IT are still very limited. Therefore, in addressing challenges with the Merdeka Belajar implementation in Islamic Schools, principals play an active role in applying related educational programs. It is advised that relevant authorities (Head of the Islamic Schools Education Section) offer both theoretical and practical support to principals and teachers regarding Merdeka Belajar.